Changes in the Neuropeptide Y mRNA Expression in Oncorhynchus mykiss at Different Feeding Frequencies. (24th August 2022) - Nahayat, Mozhdeh; Zakeri, Mohammad; Salati, Amir Parviz; Qasemi, Seyed Ahmad
Abstract : In this study, the relationship between feeding time preference and appetite in Oncorhynchus mykiss with scheduled feeding frequencies was investigated using neuropeptide Y (NPY). Samples (n = 288, initial weight: 38.72 ± 2.99 g) were stocked in three treatments of different feeding frequencies with six replications. Treatments included one feeding time at 09:00 (T1), three feeding times at 09:00, 13:00, and 17:00 (T2), and five feeding times at 09:00, 11:00, 13:00, 15:00, and 17:00 (T3) every day based on 5% of body weight for 30 days. On day 31, each experimental treatment was divided into fed and unfed groups with triplicates. To measure NPY expression, fish were sampled from both groups 15 minutes earlier than feeding hours. In a comparison of the NPY expression in T1 of the fed group, the highest level of NPY occurred at 08:45. In T2, the NPY was maximized at 08:45, 12:45, and 16:45. In T3, the NPY increased significantly at 08:45 compared to the other sampling hours. In T1 and T2 of the unfed group, the highest NPY was recorded at 10:45 and 14:45, respectively. In T3, upward and downward changes in the NPY were observed from 08:45 to 12:45 and from 12:45 to 16:45, respectively. Concerning changes in the NPY levels, the fed groups in the three treatments were significantly different at all hours, except for 08:45. In the unfed groups, significant differences were recorded between the treatments at 10:45 and 14:45. According to the fish appetite, it can be concluded that feeding O. mykiss three times a day at about 4 h intervals may be appropriate.